Agriculture, Aid and Economic Growth in Africa - McArthur, John W.; Sachs, Jeffrey D. (World Bank, Washington, DC, 2018)
How can foreign aid to agriculture support economic growth in Africa? This paper constructs a geographically-indexed applied general equilibrium model that considers pathways through which aid might affect growth and structural transformation of labor markets in the context of soil nutrient variation, minimum subsistence consumption requirements, domestic transport costs, labor mobility and constraints to self-financing of agricultural inputs. Using plausible parameters, the model is presented for Uganda as an illustrative case. Three stylized scenarios demonstrate the potential economy-wide impacts of both soil nutrient loss and replenishment, and how foreign aid can be targeted to support agricultural inputs that boost rural productivity and shift labor to boost real wages. One simulation shows how a temporary program of targeted official development assistance (ODA) for agriculture could generate, contrary to traditional Dutch disease concerns, an expansion in the primary tradable sector and positive permanent productivity and welfare effects, leading to a steady decline in the need for complementary ODA for budget support.